2016
DOI: 10.1371/journal.pntd.0005100
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Manifestations of Cutaneous Leishmaniasis in a Region Endemic for Leishmania braziliensis: Clinical, Immunological and Parasitological Aspects

Abstract: BackgroundAtypical cutaneous leishmaniasis (ACL) has become progressively more frequent in Corte de Pedra, Northeast Brazil. Herein we characterize clinical presentation, antimony response, cytokine production and parasite strains prevailing in ACL.Methodology/Principal FindingsBetween 2005 and 2012, 51 ACL (cases) and 51 temporally matched cutaneous leishmaniasis (CL) subjects (controls) were enrolled and followed over time in Corte de Pedra. Clinical and therapeutic data were recorded for all subjects. Cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 44 publications
2
76
1
1
Order By: Relevance
“…Specifically, it has been shown that there are six haplotypes presented in four loci of the chromosome 28 of L. (V.) braziliensis that are associated with DL . It has been also documented that some haplotypes in the chromosome 28 are also associated with failure to antimony therapy, indicating the importance of differences intraspecies not only in the presentation of the disease, but also in failure to therapy . However, there is a lack of data about the biological behaviour of isolates from DL on phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been shown that there are six haplotypes presented in four loci of the chromosome 28 of L. (V.) braziliensis that are associated with DL . It has been also documented that some haplotypes in the chromosome 28 are also associated with failure to antimony therapy, indicating the importance of differences intraspecies not only in the presentation of the disease, but also in failure to therapy . However, there is a lack of data about the biological behaviour of isolates from DL on phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been also documented that some haplotypes in the chromosome 28 are also associated with failure to antimony therapy, indicating the importance of differences intraspecies not only in the presentation of the disease, but also in failure to therapy. 12,13 However, there is a lack of data about the biological behaviour of isolates from DL on phagocytic cells. Neutrophils migrate quickly to the sites of infection and are the main phagocytic cells in the initial phase of L. (V.) braziliensis infection.…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian Ministry of Health defines therapeutic failure as an unsatisfactory response to two regular and sequential courses of treatment 2 . Although the therapeutic response to MA may present regional differences 6,7,8 resistance to antimonials is not a national public health problem, and 50 to 100% of the patients with an unfavorable response to the initial treatment respond satisfactorily to a second course of treatment with the same therapeutic scheme 2,9 . If a therapeutic failure ensues, the use of a secondchoice drug such as amphotericin B (desoxycholate or liposomal forms) or pentamidine isethionate 2 is suggested.…”
Section: Introductionmentioning
confidence: 99%
“…The main factors responsible for the delays or difficulties in arriving at the diagnosis of CL were usually clinical presentations mimicking other diseases [17,18]. A high index of suspicion and including CL in the differential diagnosis of granulomatous cutaneous conditions are very important for early diagnosis obecność licznych amastygotów gatunku Leishmania zarówno w monocytach, jak i w macierzy zewnątrzkomórkowej (ryc.…”
Section: Discussionmentioning
confidence: 99%
“…Wśród głównych czynników odpowiedzialnych za opóźnienia lub trudności z ustaleniem rozpoznania CL wymieniano zwykle obraz kliniczny imitujący inne choroby [17,18]. Istotne znaczenie dla odpowiednio wczesnego rozpoznania i szybkiego podjęcia leczenia tej oszpecającej choroby ma duża czujność diagnostyczna oraz uwzględnianie CL w diagnostyce różnicowej ziarniniakowych chorób skóry.…”
Section: Discussionunclassified